2016
DOI: 10.1080/15226514.2016.1244155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pisolithus tinctorius and Cenococcum geophilum inoculation on pine in copper-contaminated soil to enhance phytoremediation

Abstract: We used Pisolithus tinctorius and Cenococcum geophilum to determine the copper (Cu) resistance of ectomycorrhizal (ECM) fungi and their potential for improving phytoremediation of Cu-contaminated soil by Chinese red pine (Pinus tabulaeformis). The results showed that nutrient accumulation in C. geophilum mycelium was significantly lower under higher Cu concentrations in the soil, which was not observed in P. tinctorius. Meanwhile, P. tinctorius exhibited greater Cu tolerance than C. geophilum. Inoculation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…In relation to this, ectomycorrhizal (ECM) fungi may provide protection against metal toxicity through avoidance (i.e., extracellular precipitation, biosorption to cell walls, reduced uptake) and sequestration (i.e., intracellular chelation, compartmentation into fungi vacuoles) ( Hartley et al, 1997 ; Jentschke and Godbold, 2000 ; Bellion et al, 2006 ). Therefore, phytoremediation of TE polluted soils can be facilitated by ECM fungi as they adapt to TE stress promoting the host growth ( Wen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to this, ectomycorrhizal (ECM) fungi may provide protection against metal toxicity through avoidance (i.e., extracellular precipitation, biosorption to cell walls, reduced uptake) and sequestration (i.e., intracellular chelation, compartmentation into fungi vacuoles) ( Hartley et al, 1997 ; Jentschke and Godbold, 2000 ; Bellion et al, 2006 ). Therefore, phytoremediation of TE polluted soils can be facilitated by ECM fungi as they adapt to TE stress promoting the host growth ( Wen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vaario et al [52] found that mushrooms of Tricholoma matsutake, and ECM fungus, were enriched in Al. Pisolithus tinctorius increased Cu accumulation in Pinus tabulaeformis and the majority of the Cu remained in the roots [53]. These results indicated that ECM fungi might limit Al 3+ movement toward the inner root tissues and then inhibit Al 3+ translocation to the shoot.…”
Section: Accumulation and Translocation Of Al In Ecm P Massoniana Sementioning
confidence: 82%
“…They play a key role in the mobilisation and uptake of organic and inorganic N and P providing access to nutrient sources not directly available to plants (Tibbett and Sanders, 2002;Cairney and Meharg, 2003), and are also known to mobilise trace metals by dissolving a variety of Cd, Cu and Zn-bearing minerals, including metal phosphates (Gadd et al, 2012). Plant species colonised by ECM and ERM fungi can also grow successfully on highly metal-contaminated sites (Colpaert et al, 2011;Saraswat and Rai, 2011;Wen et al, 2017). They exhibit decreased sensitivity to a wide range of essential and non-essential metals including Cd, Zn, Ni and Cu, however, metal tolerance or sensitivity varies widely between plant and mycorrhizal species (Bradley et al, 1982;Bücking and Heyser, 1994;Chen and Tibbett, 2007;Frey et al, 2000;Gadd et al, 2012;Hartley-Whitaker et al, 2000;Hrynkiewicz and Baum, 2013;Sell et al, 2005;Mrnka et al, 2012).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%